2018
DOI: 10.1002/cncr.31125
|View full text |Cite
|
Sign up to set email alerts
|

Targeting HER2 in colorectal cancer: The landscape of amplification and short variant mutations in ERBB2 and ERBB3

Abstract: BACKGROUNDIn contrast to lung cancer, few precision treatments are available for colorectal cancer (CRC). One rapidly emerging treatment target in CRC is ERBB2 (human epidermal growth factor receptor 2 [HER2]). Oncogenic alterations in HER2, or its dimerization partner HER3, can underlie sensitivity to HER2‐targeted therapies.METHODSIn this study, 8887 CRC cases were evaluated by comprehensive genomic profiling for genomic alterations in 315 cancer‐related genes, tumor mutational burden, and microsatellite ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
116
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(140 citation statements)
references
References 94 publications
9
116
2
Order By: Relevance
“…In the present analysis, we observed a 6.7% incidence of HER2 positivity, in line with studies highlighting a higher incidence of HER2 positivity among patients without KRAS mutations than in the unselected population [5]. We found that HER2 positivity was associated with the presence of lung metastases and a higher tumor burden.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the present analysis, we observed a 6.7% incidence of HER2 positivity, in line with studies highlighting a higher incidence of HER2 positivity among patients without KRAS mutations than in the unselected population [5]. We found that HER2 positivity was associated with the presence of lung metastases and a higher tumor burden.…”
Section: Discussionsupporting
confidence: 92%
“…In metastatic colorectal cancer (mCRC), the rate of HER2 amplification or overexpression ranges from 1.3% to 3.2% of cases in all stages, molecularly unselected , up to 5.2% in KRAS exon 2 wild‐type patients in the metastatic setting . In a recent study performed in a large cohort of colorectal cancer (CRC) samples from stage IV patients by next‐generation sequencing (NGS) of a panel of 315 cancer‐related genes, amplification of ERBB2 was found in 2.8%, and KRAS mutations were found to occur less frequently in ERBB2 ‐amplified samples .…”
Section: Introductionmentioning
confidence: 99%
“…ERBB2/HER2 expression in the WT tumor was also significantly higher than in any of our 19 reference proteomes. The opportunity to target ERBB2/HER2 in colorectal cancer has recently emerged [43] as it is amplified and/or mutated in 5% of CRC tumors, most often in KRAS WT tumors [43], which agrees with our data.…”
Section: Quantitative Comparison Of Kras G12v and Kras Wt Tumorssupporting
confidence: 91%
“…59 Alterations in Her-2 signaling, either through genomic amplification or mutations is tumor promoting, and anti-HER2 therapies for preventing CRC recurrence and are a focus of on-going work. 60 We finally note that MAPK and PI3K-AKT signaling cascades are implicated in many of the above discussed pathways.…”
Section: Spatial Domain Network Reveal Domain-specific Network Biolomentioning
confidence: 88%